Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Certainly! Let's work through the factorization step-by-step.
Given expression:
[tex]\[ 2x^2 - xy - 6y^2 \][/tex]
We need to factorize this quadratic expression. To do this, we look for two binomials whose product equals the given expression. Let's denote these binomials as:
[tex]\[ (Ax + By)(Cx + Dy) \][/tex]
First, we expand the product of these two binomials:
[tex]\[ (Ax + By)(Cx + Dy) = ACx^2 + ADxy + BCxy + BDy^2 \][/tex]
Combining like terms:
[tex]\[ (Ax + By)(Cx + Dy) = ACx^2 + (AD + BC)xy + BDy^2 \][/tex]
Now, compare this expanded form with our given expression [tex]\( 2x^2 - xy - 6y^2 \)[/tex]:
Matching coefficients, we get:
[tex]\[ \begin{cases} AC = 2 \\ AD + BC = -1 \\ BD = -6 \end{cases} \][/tex]
We need to find values of [tex]\( A, B, C, \)[/tex] and [tex]\( D \)[/tex] that satisfy these conditions.
Let's try to find suitable values step-by-step:
1. Find [tex]\( A \)[/tex] and [tex]\( C\)[/tex]:
[tex]\[ AC = 2 \][/tex]
Possible pairs [tex]\((A, C)\)[/tex] could be [tex]\((1, 2)\)[/tex], [tex]\((2, 1)\)[/tex], [tex]\((-1, -2)\)[/tex], [tex]\((-2, -1)\)[/tex].
2. Find [tex]\( B \)[/tex] and [tex]\( D\)[/tex]:
[tex]\[ BD = -6 \][/tex]
Possible pairs [tex]\((B, D)\)[/tex] could be [tex]\((1, -6)\)[/tex], [tex]\((-1, 6)\)[/tex], [tex]\((2, -3)\)[/tex], [tex]\((-2, 3)\)[/tex], [tex]\((3, -2)\)[/tex], [tex]\((-3, 2)\)[/tex], [tex]\((6, -1)\)[/tex], [tex]\((-6, 1)\)[/tex].
We substitute these pairs into the second equation ([tex]\(AD + BC = -1\)[/tex]) to check which pair works.
Check pair [tex]\( (A = 1, C = 2) \)[/tex]:
- If [tex]\(A = 1\)[/tex] and [tex]\(C = 2\)[/tex], then [tex]\( AD + BC = 1\cdot D + 2\cdot B = -1 \)[/tex]:
- Try [tex]\( B = 3, D = -2\)[/tex]:
[tex]\[ 1\cdot (-2) + 2\cdot 3 = -2 + 6 = 4 \quad \text{(not correct)}\][/tex]
- Try [tex]\( B = -3, D = 2 \)[/tex]:
[tex]\[ 1\cdot 2 + 2\cdot (-3) = 2 - 6 = -4 \quad \text{(not correct)}\][/tex]
Check pair [tex]\( (A = 2, C = 1) \)[/tex]:
- If [tex]\(A = 2\)[/tex] and [tex]\(C = 1\)[/tex], then [tex]\( AD + BC = 2\cdot D + 1\cdot B = -1 \)[/tex]:
- Try [tex]\( B = -3, D = 1 \)[/tex]:
[tex]\[ 2\cdot 1 + 1\cdot (-3) = 2 - 3 = -1 \quad \text{(correct)}\][/tex]
Since pair [tex]\( (A = 2, D = 1)\)[/tex] and [tex]\( (C = 1, B = -3)\)[/tex] satisfy the conditions, our factors are:
[tex]\[ (2x + 3y)(x - 2y) \][/tex]
Thus, the factorized form of the given expression is:
[tex]\[ 2x^2 - xy - 6y^2 = (x - 2y)(2x + 3y) \][/tex]
Given expression:
[tex]\[ 2x^2 - xy - 6y^2 \][/tex]
We need to factorize this quadratic expression. To do this, we look for two binomials whose product equals the given expression. Let's denote these binomials as:
[tex]\[ (Ax + By)(Cx + Dy) \][/tex]
First, we expand the product of these two binomials:
[tex]\[ (Ax + By)(Cx + Dy) = ACx^2 + ADxy + BCxy + BDy^2 \][/tex]
Combining like terms:
[tex]\[ (Ax + By)(Cx + Dy) = ACx^2 + (AD + BC)xy + BDy^2 \][/tex]
Now, compare this expanded form with our given expression [tex]\( 2x^2 - xy - 6y^2 \)[/tex]:
Matching coefficients, we get:
[tex]\[ \begin{cases} AC = 2 \\ AD + BC = -1 \\ BD = -6 \end{cases} \][/tex]
We need to find values of [tex]\( A, B, C, \)[/tex] and [tex]\( D \)[/tex] that satisfy these conditions.
Let's try to find suitable values step-by-step:
1. Find [tex]\( A \)[/tex] and [tex]\( C\)[/tex]:
[tex]\[ AC = 2 \][/tex]
Possible pairs [tex]\((A, C)\)[/tex] could be [tex]\((1, 2)\)[/tex], [tex]\((2, 1)\)[/tex], [tex]\((-1, -2)\)[/tex], [tex]\((-2, -1)\)[/tex].
2. Find [tex]\( B \)[/tex] and [tex]\( D\)[/tex]:
[tex]\[ BD = -6 \][/tex]
Possible pairs [tex]\((B, D)\)[/tex] could be [tex]\((1, -6)\)[/tex], [tex]\((-1, 6)\)[/tex], [tex]\((2, -3)\)[/tex], [tex]\((-2, 3)\)[/tex], [tex]\((3, -2)\)[/tex], [tex]\((-3, 2)\)[/tex], [tex]\((6, -1)\)[/tex], [tex]\((-6, 1)\)[/tex].
We substitute these pairs into the second equation ([tex]\(AD + BC = -1\)[/tex]) to check which pair works.
Check pair [tex]\( (A = 1, C = 2) \)[/tex]:
- If [tex]\(A = 1\)[/tex] and [tex]\(C = 2\)[/tex], then [tex]\( AD + BC = 1\cdot D + 2\cdot B = -1 \)[/tex]:
- Try [tex]\( B = 3, D = -2\)[/tex]:
[tex]\[ 1\cdot (-2) + 2\cdot 3 = -2 + 6 = 4 \quad \text{(not correct)}\][/tex]
- Try [tex]\( B = -3, D = 2 \)[/tex]:
[tex]\[ 1\cdot 2 + 2\cdot (-3) = 2 - 6 = -4 \quad \text{(not correct)}\][/tex]
Check pair [tex]\( (A = 2, C = 1) \)[/tex]:
- If [tex]\(A = 2\)[/tex] and [tex]\(C = 1\)[/tex], then [tex]\( AD + BC = 2\cdot D + 1\cdot B = -1 \)[/tex]:
- Try [tex]\( B = -3, D = 1 \)[/tex]:
[tex]\[ 2\cdot 1 + 1\cdot (-3) = 2 - 3 = -1 \quad \text{(correct)}\][/tex]
Since pair [tex]\( (A = 2, D = 1)\)[/tex] and [tex]\( (C = 1, B = -3)\)[/tex] satisfy the conditions, our factors are:
[tex]\[ (2x + 3y)(x - 2y) \][/tex]
Thus, the factorized form of the given expression is:
[tex]\[ 2x^2 - xy - 6y^2 = (x - 2y)(2x + 3y) \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.